Improving affirming care for sexual and gender minority veterans - Valentine, Sarah E. (Psychol Serv, 2019)
Lesbian, gay, bisexual, and transgender (LGBT) populations face a range of health disparities that all health care systems must address. In response to known health disparities, the LGBT Health Program of the Veterans Health Administration (VHA) developed policies supporting the provision of affirming care to LGBT veterans. To support policy implementation, the program launched the LGBT Veteran Care Coordinator (LGBT VCC) Program in 2016, requiring every VHA facility to appoint at least one clinical staff member to serve as an LGBT VCC. This quality improvement project reports on LGBT VCCs’ perspectives on the state of affirming care at their facilities in the first year of the program. LGBT VCCs (n=79) completed a brief online survey, including qualitative questions on barriers and facilitators to implementation, and general recommendations for the program. The Consolidated Framework for Implementation Research (CFIR) guided directed content analysis of reported facilitators and barriers. The highest proportion of facilitators and barriers reported by the LGBT VCCs were coded under leadership engagement, available resources, other personal attributes, organizational culture, and networking and communications. LGBT VCCs requested additional support in securing adequate designated administrative time, engaging with facility leadership, improving networking and communication, tailoring programing, and providing professional advancement opportunities. Organizing findings using the CFIR enabled the LGBT Health Program to effectively promote facilitators and address barriers experienced during the startup year of the LGBT VCC Program. VHA’s efforts to reduce LGBT veteran health disparities may serve as a model for other health care systems.